Estudo de vida de ferramentas de corte de uma empresa do setor metalmecânico - Monteiro, Elvis Presley (2014)
The market demands of business agility, flexibility to meet demands, intense customer focus, shortened life cycles of products, constant development of new technologies, the challenge of reducing costs and high quality manufacturing. Significant portions of costs in this segment are represented by processes of machining components, and a large portion of these costs is related to the use of cutting tools. Within this context, the efficient management of cutting tools becomes important element to reduce costs and eliminate waste. This case study was performed in a mechanical engineering company in the industry, where he works with serial production of parts for the automotive industry. The study was specified due to the turning process, which was the correct tool selection, we analyzed the consumption of cutting edges and training operators for possible replacements and correct adaptation of cutting parameters to become the most appropriate to case. Also sought to reduce liabilities times involving human tasks, or reduction of productive time, when considering the machining process. The reduction of liabilities times can be achieved with implementation of management techniques or tools like Kanban, Poka Yoke, or other tools. The productive time can also be reduced by acquiring new machines, tools, devices and also with cutting parameters, reduction of metal or by cutting study that defines the cutting path during the course of machining tool strategy. Therefore, the methodology used consisted of descriptive research and direct observation of processes to reduce total cost of machining a part in serial production and identify and discuss the perspective of production, the main practices related to the management of cutting tools in industry. For this, experiments were carried out varying the parameters of the cutting speed and feed, while maintaining fixed depth of machining. The lifetime results found for the coated tools showed the intensity of the changes that occur in the two predominant mechanisms of wear, adhesion and abrasion. Where in the processing of different volumes of production and in decreasing processing times, or, in the minimization of tool switches.